2021
DOI: 10.24093/awej/vol12no4.14
|View full text |Cite
|
Sign up to set email alerts
|

Pronunciation Problems Encountered by EFL Learners: An Empirical Study

Abstract: Arabs often mispronounce many sounds of English due to a lack of exposure to English as a foreign language. This research article focuses on pronunciation problems encountered by Arab undergraduate EFL learners. It uses questionnaires, recorded speech samples, and pronunciation tests as part of its methodology to analyze learners’ performance orally through repetition drills to help participants articulate the sounds of English through Blackboard Collaborate Ultra Learning Management System. This research emph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Dalam kelas-kelas EFL (English as Foreign Language) terdapat beberapa masalah dalam pelaksanaan pembelajaran Bahasa Inggris seperti Bahasa Inggris tidak digunakan sebagai alat komunikasi dimana kelas-kelas tidak secara aktif menerapkan bahasa inggris baik ketika menyampaikan materi pembelajaran maupun memberikan jawaban (Zainil & Arsyad, 2021). Fenomena bahasa Inggris pasif dalam pembelajaran juga berakibat pada siswa yang kesulitan melafalkan kosa kata bahasa Inggris dengan benar karena tidak ada contoh langsung yang dapat mereka lihat (Jahara & Abdelrady, 2021). Masalah lainnya adalah kesulitan mengeja huruf dalam kosa kata bahasa Inggris, hal tersebut terjadi ketika kosa kata yang muncul kurang familiar (Gerlach, 2017).…”
Section: Pendahuluanunclassified
“…Dalam kelas-kelas EFL (English as Foreign Language) terdapat beberapa masalah dalam pelaksanaan pembelajaran Bahasa Inggris seperti Bahasa Inggris tidak digunakan sebagai alat komunikasi dimana kelas-kelas tidak secara aktif menerapkan bahasa inggris baik ketika menyampaikan materi pembelajaran maupun memberikan jawaban (Zainil & Arsyad, 2021). Fenomena bahasa Inggris pasif dalam pembelajaran juga berakibat pada siswa yang kesulitan melafalkan kosa kata bahasa Inggris dengan benar karena tidak ada contoh langsung yang dapat mereka lihat (Jahara & Abdelrady, 2021). Masalah lainnya adalah kesulitan mengeja huruf dalam kosa kata bahasa Inggris, hal tersebut terjadi ketika kosa kata yang muncul kurang familiar (Gerlach, 2017).…”
Section: Pendahuluanunclassified
“…Indonesian students do not habitually use English as means of communication in their society even though it is normally taught in schools from the earliest level of education nowadays (Mutiah et al, 2020). This lack of practice might lead them to the major problems that students are mostly having difficulties in producing certain English sounds (Farhat Jahara & Hussein Abdelrady, 2021). This statement is also supported by previous research which found that there are five factors affecting students' difficulties in mastering English pronunciation: 1) the influences of native language, lack of motivation, lack of practice, the influence of students' environment, and lack of selfconfidence (Antaris & Omolu, 2019).…”
Section: Introductionmentioning
confidence: 99%